Adverse Impacts of Changing Climatic Conditions on the Environment due to increasing Pollution - Piyush Gupta (International Journal of Life Sciences, 2015)
This paper deals with the different perceptions about global environmental crisis due to the over burden of pollution. Environmental problems are not as bad as they are made out to be. The earth is a self-evolving and self-regulating living system and it will survive (Gaia Theory). The common issues associated with the earth’s environment are Environmental pollution, Water scarcity, Contamination of food, Waste management, Global Climate Change, Land degradation, Desertification (80% of forests are destroyed), Acid Rain, Ozone Layer Depletion, Soil Erosion, Loss of Biodiversity and Mass extinction (Most species are endangered and 50% may go extinct by 2025) etc.